Hubungan Kadar Fe ASI Dengan Kadar Hemoglobin (Hb) pada Bayi di Kecamatan Mestong tahun 2022 - Elda Yanti; M Zulkarnain; Rostika Flora; Risnawati Tanjung; Sri Martini; Indah Yuliana (Universitas Batanghari Jambi, 2022)
Iron has an important role in the process of neurotransmitter synthesis and myelination of neurons. Lack of iron consumption in the daily diet can cause anemia which is characterized by a decrease in blood hemoglobin levels. Low levels of hemoglobin cause slower growth in infants, which can lead to stunting. One of the main sources of Fe intake in infants is Fe which comes from breast milk given by the mother. This study aims to determine the relationship between Fe levels in breast milk and Hemoglobin levels in infants in Mestong District in 2022. This research is quantitative analytic with a cross sectional approach. The study was conducted in Mestong District (Tempino Public Health Center and Pondok Table Health Center) in March-April 2022. The population in this study were all breastfeeding mothers and their infants and children aged 0-23 months as many as 3,231 people. The sample in this study was 61 people who were taken using a proportional consecutive sampling technique. The examination of Fe levels in breast milk was carried out by Spectrophotometry, while the hemoglobin levels of infants were checked using a Digital Hb analyzer whose results were calibrated/standardized with the results of blood chemistry Hb. The results showed that statistically there was no relationship between Fe levels in breast milk and hemoglobin levels in infants. However, from 8 mothers whose milk Fe levels were normal, 100% of the hemoglobin levels of their babies and children were in the normal category. Meanwhile, from 53 mothers with low Fe levels in breast milk, as many as 30.2% of their infants and children had low hemoglobin levels.